Eco-friendly Single Bath Dyeing and Ultraviolet Protective Finishing of Proteinous Fabric Using Loganin Derived Blue Dye. Issue 12 (1st December 2020) - Patil, Sapna P.; Pandit, Pintu; Laddha, Kirti S.
ABSTRACT: The present work mainly deals with the study of blue colored dye, synthesized from an iridoid glycoside loganin from strychnos fruits ( Strychnos nux-vomica ). The efficacy of synthesized blue dye was studied with proteinous fabric such as wool and silk using different types of mordants, namely, tannic acid, myrobalan, alum. The dyeing of fabric was carried out by techniques such as pre-mordanting, meta-mordanting, and post-mordanting. The color strength (K/S) of wool fabric was found to be higher in case of the meta-mordanting method using alum as a mordant as compared to pre and post-mordanting techniques. Treated fabrics showed adequate wash, light and rubbing properties with and without mordanting. The treated silk and wool fabric showed good to very good ultraviolet protection property with mordanted fabric. In vitro toxicity studies by hemolytic and phytotoxicity assay was performed to check for the safety of the dye as a colorant.